The Impact of Orthodontic Forces on the Occurrence of Iatrogenic Tooth Root Resorption - Nino Tsilosani; Ana Galogre; Natia Natsvlishvili (European Scientific Journal, ESJ, 2022)
Modern orthodontic treatment ensures optimal functional and aesthetic results, but does not exclude the risk of various complications, including external or internal resorption of tooth roots. One of the causes of root resorption is the impact of orthodontic forces during treatment with both non-removable (brace-system) and removable (aligners) appliances. The aforementioned complication of the treatment of occlusal anomalies, which occurs with a fairly high frequency, potentially threatens not only the patient's health, but also complicates the treatment outcomes and worsens the prognosis. The lack of pathognomonic symptoms of root resorption increases the difficulty of an accurate diagnosis. According to the literature, the issue of root resorption is very relevant in clinical dentistry but has not been studied in detail, and contradictory opinions can be found.